Health professionals as advocates for climate solutions: A case study from Wisconsin, - Joel Charles; Abby N. Lois; Chirantan Mukhopadhyay; Edward Maibach; Jonathan A. Patz (Elsevier, 2021)
Health professionals are in a unique position to accelerate the creation of policies to mitigate and adapt to the public health emergency that is the climate crisis. At the forefront of the burgeoning climate and health movement are state and national health professional networks that are educating their colleagues and the lay public about the gravity of this threat and advocating for equitable solutions. Here we present a case of one such group, Wisconsin Health Professionals for Climate Action (WHPCA), highlighting its organizational structure and path to success. We also present a logic map to help understand the primary leverage points for health professional advocacy.